Concise Encyclopedia of High Performance Silicones - Tiwari, Atul.; Soucek, Mark D. (Salem, Mass. : Scrivener Publishing ; Hoboken, New Jersey : Wiley, 2014)
The encyclopedia will be an invaluable source of information for researchers and students from diverse backgrounds including physics, chemistry, materials science and surface engineering, biotechnology, pharmacy, medical science, and biomedical engineering.
3.3.4 Recommendation3.4 High Functionality Resins for the Fabrication of Nanocomposites; 3.4.1 Mechanical Properties; 3.4.2 Thermo-Mechanical Behavior; 3.4.3 Thermal Properties; 3.4.4 Flame Retardancy Studies; 3.4.5 Effect of Curing Agent towards Flame Retardancy; 3.4.6 Nano Reinforcement (POSS) Effect towards Flame Retardancy; 3.4.7 Highlights; 3.5 Anticorrosive and Antifouling Coating Performance of Siloxane- and Phosphorus-Modified Epoxy Composites; 3.5.1 Results of Potentiodynamic Polarization Study; 3.5.2 Results of Electrochemical Impedance Study (EIS); 3.5.3 Salt Spray Test Results.
3.5.4 Results from Antifouling Studies.
Includes bibliographical references and index.
Print version record.
Keywords: Silicones -- Encyclopedias; Silicones -- Industrial applications -- Encyclopedias; Silicones -- Encyclopedias; Silicones -- Industrial applications -- Encyclopedias; Technology and engineering -- Material science; TECHNOLOGY & ENGINEERING -- Material Science; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Electronic books